Anxiety Disorder in Donna Tartt’s the Goldfinch - Abu Fanani; Machfud Muhamad Sodiq; Fathur Rohim; Akhmad Syaikhu; Muhammad Thoriqussuud (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Tartt’s the Goldfinch is an anxiety disorder novel experienced by the main character, Theo, because he cannot fulfill his desires. The main cause of his desire fulfillment inability is the death of his beloved mother, the separation from his beloved girlfriend, and his dealing with criminal. How the main character experiences the anxiety disorder and factors of the anxiety disorder become the purpose of the researcher’s study. Anxiety’s types: neurotic anxiety, moralistic anxiety, and realistic anxiety as well as descriptive and dramatic method would be of any use because the researcher can conduct a deep observation about anxiety disorder’s symptoms experienced by the main character that is depression, trauma, panic, and frustration. Accordingly, the study finds that the main character experiences those mentioned types of anxiety through depression, trauma, panic, and frustration caused by his inability in controlling his emotion as well as his social carelessness. Eventually, the study gives contribution to development of the literary study specifically in dealing with anxiety.